Cognitive and functional status in late-onset Lennox–Gastaut syndrome: Variation on a classic phenotype - Chourasia, Nitish; Maheshwari, Atul; Kalamangalam, Giridhar (Epilepsy & behavior, 2020)
Lennox–Gastaut syndrome (LGS) denotes a refractory epileptic encephalopathy of childhood onset with the triad of generalized slow spike–wave (GSSW) on interictal scalp electroencephalogram (EEG), multiple seizure types, and intellectual impairment. The neurobiology of LGS is said to sustain abnormal patterns of brain activity and connectivity that ultimately impair normal cerebral developmental mechanisms. However, we describe eight patients from our combined practice who presented with electroclinical findings consistent with LGS but without significant cognitive impairment. All patients fulfilled the other criteria of LGS with multiple seizure types (three or more of generalized tonic–clonic, atonic, tonic, myoclonic, and atypical absence) and GSSW activity on EEG. Four subjects completed high school, two completed some college, two acquired college degrees, and all performed basic and instrumental activities of daily living (ADL) independently. Magnetic resonance imaging (MRI) was normal in all patients. We speculate that a variation of the classic phenotype of LGS can present with preserved cognitive and functional status, often with onset in the second decade of life, and associated with normal brain imaging.